Adhyātma-darśana : Ānandaghana Caubīsī para padamagnabhāshya - Nemicandra, Muni, 1921- (Viśvavātsalya Prakāśana Samiti, 1976)
Commentary, with Gujarati text, on Caubīsī of Maha Yogi Ānandaghana, 18th cent., verses on twentyfour Jaina Tīrthaṅkaras; interpretation embracing Jaina ethics, ontology, and religion.